MENINGKATKAN MINAT BELAJAR SISWA KELAS III SDN MODEL TERPADU MADANI PALU MATERI OPERASI HITUNG PEMBAGIAN BILANGAN CACAH SAMPAI 100 MELALUI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) - Ni Ketut Yuniasti; Astija; Paul Rumondor (EDU RESEARCH, 2024)
This study aims to improve students' learning interest through the implementation of the Teaching at the Right Level (TaRL) Approach in mathematics learning on the material of arithmetic operations of dividing whole numbers up to 100 in class III of SDN Model Terpadu Madani Palu. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of this study were 30 students in class III. Data were collected through observation, tests, and documentation, then analyzed descriptively to see the increase in students' learning interest. The indicator of success in this study was the achievement of 80% of students who had a high interest in learning. The results showed that the implementation of TaRL significantly increased students' learning interest, which was marked by an increase in the percentage of achievement from 40% in the pre-cycle, 78.75% in Cycle I, and 90% in Cycle II. These findings indicate that a learning approach that is adjusted to students' ability levels can increase students' motivation and involvement in the learning process. Thus, it is recommended that TaRL be integrated more widely in learning to support the improvement of students' learning interest and their academic results.